2000
DOI: 10.1007/bf02942972
|View full text |Cite
|
Sign up to set email alerts
|

The risk of toxins byFusarium graminearum in wheat — interactions between weather and agronomic factors

Abstract: In the course of a Fusarium Monitoring for winter wheat in Bavaria five deoxynivalenol risk factors have been identified. The major Fusarium species wasF. graminearum, which usually has one disease cycle; under specific weather conditions obviously a bicyclic spread of the pathogen occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 2 publications
0
12
0
Order By: Relevance
“…(Obst et al 2000). The results shown inTables 1, 2, 3, and 4 demonstrate that cereals from the harvests of years 2002 and 2007 had a higher toxin contamination than that of the other years.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…(Obst et al 2000). The results shown inTables 1, 2, 3, and 4 demonstrate that cereals from the harvests of years 2002 and 2007 had a higher toxin contamination than that of the other years.…”
mentioning
confidence: 78%
“…Organic cultivation is characterized by the omission of maize as previous crop, traditional tillage, and by selection of relatively Fusarium-resistant cultivars. Furthermore, renunciation of using plant protectant and other chemicals such as fungicides or growth regulators (retardants) which are applied in integrated cultivation could contribute to the relatively low Fusarium contamination (and thus of the low toxin contents) in organically cultivated cereals (Meier et al 2000;Obst et al 2000;Oldenburg 2004). …”
Section: Discussionmentioning
confidence: 99%
“…Organic cultivation is characterized by the omission of maize as previous crop, traditional tillage, and by selection of relatively Fusarium-resistant cultivars. Furthermore, the ban of plant protectants and other chemicals such as fungicides or growth regulators (retardants) which are applied in integrated cultivation could contribute to the relatively low Fusarium contamination (and thus of the low toxin contents) in organically cultivated cereals (Meier et al, 2000;Obst et al, 2000;Oldenburg, 2004;Meister, 2009). Döll et al (2002), reported that in the case of non fungicide treatment, wheat from organic farming is more tolerant to Fusarium infection than wheat from conventional farming systems.…”
Section: Resultsmentioning
confidence: 99%
“…metconazole and tebuconazole, were shown to be effective, particularly in experiments with additional Fusarium inoculation resulting in reductions of head blight severity and mycotoxin contamination by 50-80% and 5-90%, respectively (Matthies and Buchenauer 2000;Pirgozliev et al 2002;Chala et al 2003;Haidukowski et al 2005). In other experiments, however, fungicide applications resulted in an increased trichothecene accumulation (Gareis and Ceynowa 1994;Obst et al 2000). Strobilurin fungicides have been reported several times to increase DON production, although they can partially control FHB (Simpson et al 2001;Lienemann et al 2002;Menniti et al 2003;Mesterhazy et al 2003).…”
Section: Introductionmentioning
confidence: 95%